Institutional change and entrepreneurship as occupational choice—The case of South Korea - Diana Schüler (Journal of International Entrepreneurship, 2022)
Even though research on the influence of institutions on entrepreneurial activities has recently gained scholarly attention, most studies are quantitative cross-country analyses that assume response homogeneity. Qualitative single-country studies that provide deeper insights into institutional peculiarities are still rare, especially in the East Asian context. Based on qualitative data generated from semi-structured interviews, this study examines the institutional environment for entrepreneurship in South Korea and its latest changes to explain the recent wave of newly established corporations. Building on Scott's distinction of institutional dimensions, this article demonstrates how significant changes in regulative institutions pushed forward by the Korean central government have decreased individual financial risks and have created a surge in business foundations. At the same time, normative institutions have remained almost unchanged, while changes of the cognitive institutional dimension in the form of entrepreneurship education are underway. The findings suggest that regulative institutions play a bigger role for entrepreneurial activities than cognitive or normative institutions, as people start a business despite unfavorable informal institutions. Theory should therefore reevaluate the importance and effective power of each institutional dimension on entrepreneurial activities. Policymakers who put high emphasis on regulative institutions should pay attention to potential moral hazards arising from generous support programs.
Keywords: L26; D02; O17; N45; O53; 330; Entrepreneurship; Institutions; Institutional change; South Korea